PEMAKNAAN DALAM PUISI JATI NISKALA KARYA DINULLAH RAYES (TINJAUAN SEMIOTIKA RIFFATERRE) - Supriadi; Sukarismanti; Jumianti Diana (MANTRA: Jurnal Sastra Indonesia (Sastra, Bahasa, Budaya), 2023)
This study aims to examine Dinullah Rayes's poetry which uses the symbol of nature, "jati" by using: (1) heuristic reading; (2) hermeneutic reading; (3) matrix; (4) models; and (5) the variants, in the Jati Niskala Poetry by Dinullah Rayes (2014). This research is library research, because the primary data and secondary data are in the form of books or related documents. The method used in this study is a qualitative descriptive method with Riffaterre's semiotic approach and the data collection technique used in this study is the documentation method. The results and conclusions of this study are as follows: (l) The importance of carrying out all the commands of Allah SWT; (2) Never give up on all the tests given by Allah SWT while living in the world; (3) The importance of establishing friendly relations with fellow human beings while living in the world; (4) The importance of not destroying and always protecting the environment; (5) Always good at being grateful for all the blessings that Allah SWT has given to humans while living in the world.